RECENT METHOD DEVELOPMENT BY ANALYTICAL TECHNIQUES OF NEW FDA APPROVED RUGS IN 2021 - PARMAR, ISHVARCHANDRA; PATEL, YOGI A (International Journal of Current Pharmaceutical Research, 2022)
In this present situation increase in the number of diseases has been observed and several new medications are invented and have been developed to treat various disorders, which are approved by FDA. But before these drugs come to market it must undergo several procedures. The validation and analytical process of a new drug development helps in ensuring its purity and reliability. This process involves the use of various analytical techniques to collect data about the drug. This review includes various types of analytical techniques such as ultraviolet-visible spectrophotometric and some chromatography methods (High-performance thin-layer chromatography, High-performance liquid chromatography, gas chromatography), hyphenation techniques such as LC-MS of the newly approved drug in the year of 2021 have been discussed.